Preparation of biological samples containing both metallic and organic structures for SEM - Gomes, Fernando Vacilotto; Baraldi, Carlos Eduardo; Ponzoni, Deise; de Oliveira, Marília Gerhardt; Puricelli, Edela (Revista de Ciências Médicas e Biológicas, 2013)
<!--[if gte mso 9]> Normal.dotm 0 0 1 166 965 UFRGS 18 4 1164 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> <!--StartFragment--> Objective: results of preclinical studies depend on high-quality sample preparation, which enables proper handling of specimens for observation and analysis with the desired methods. The aim of this paper is to describe a step-by-step method for preparation of bone tissue specimens containing metallic implants for scanning electron microscopy (SEM). Methodology: eight rabbit bone specimens containing one osseointegrated implant each were fixated in 10% neutral buffered formalin, dehydrated, sectioned, and embedded in thermosetting resin. The specimens were then sanded, polished, and metal-coated for SEM analysis. Results: the method achieved satisfactory specimen surface smoothness, containing no cracks or other artifacts, enabling morphological and chemical analysis by means of SEM and energy-dispersive X-ray spectroscopy (EDS). Conclusion: this method for preparation of animal tissue samples containing both organic and metal components produced specimens amenable to SEM analysis with excellent image quality, enabling assessment of the bone–implant interface, measurement of bone–implant contact, and quantification of bone formation. <!--EndFragment-->